Opportunities for Using Technology Industry 4.0 to Overcome the Negative Effect of The Covid-19 Pandemi - Setiawan, Sigit; Poerbosisworo, Ishelina Rosaira (Jurnal Pekommas, 2021)
Currently the Covid-19 pandemic has affected us a lot, both in personal behavior, or especially in the economic sector which continues to deteriorate due to the closure of regions and / or restrictions on human movement. Many companies have closed, and many have become bankrupt because they had to close their companies. Various stimulus programs and efforts have been made by both the companies themselves and each countries to overcome this problem. On the other hand, in Indonesia the concept of Industry 4.0, which is currently developing rapidly, was proclaimed by President Joko Widodo at the beginning of his second term government. The concept of Industry 4.0 has been developed since 2015 and is now still under developing to be applied in the world. This concept is based on digitalization and ICT networks to carry out production. In addition, the goal of the industrial 4.0 concept is to produce a production system capable of producing revolutionary system that can produce customized product taht being produce in mass production way and therefore able to open up a new market niche. Since then, there are much progress been done by the government in its efforts to apply the industry 4.0 concept to all lines. But the problem is, is it true that what is being implemented is industry 4.0? Also, will the technologies and management concepts promoted by Industry 4.0 be able to overcome the current Covid-19 pandemic conditions if they have been implemented? This paper seeks to explore this theoretically, by looking at key technologies from Industry 4.0 that might solve the problem of the Covid-19 pandemic. There are several technologies from Industry 4.0 that can overcome the conditions of the Covid-19 pandemic, for example AI and Additive manufacturing. It is hoped that from the results of this research experience can be drawn for the application of industry 4.0, especially during the current Covid-19 pandemic.Keywords: Industry 4.0, Covid-19 Pandemic, industry challenges